Relación entre la calidad de servicio y la satisfacción del consumidor: Su evaluación en el ambito del turismo termal - M. E. Alén González; J. A. Fraiz Brea (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2006)
Service quality and satisfaction are constructs that have received so much attention in marketing literature; they had been the central elements of many investigations. However, the relationship between them is not still clear. Because of it, in the present work, a model which picks up the causal relationships for both is empirically contrasted. Specifically, we expect to evaluate in thermal tourism context, if the relationship between both constructs is bidirectional (satisfaction as an antecedent of service quality and at the same time, consequent) or unidirectional (satisfaction as antecedent or consequent of service quality).
Keywords: 330; service quality; satisfaction; thermal tourism; confirmatory factor analysis